2022
DOI: 10.1007/s00330-021-08485-6
|View full text |Cite
|
Sign up to set email alerts
|

Lung vessel volume evaluated with CALIPER software is an independent predictor of mortality in COVID-19 patients: a multicentric retrospective analysis

Abstract: Introduction Computer-Aided Lung Informatics for Pathology Evaluation and Ratings (CALIPER) software has already been widely used in the evaluation of interstitial lung diseases (ILD) but has not yet been tested in patients affected by COVID-19. Our aim was to use it to describe the relationship between Coronavirus Disease 2019 (COVID-19) outcome and the CALIPER-detected pulmonary vascular-related structures (VRS). Materials and methodsWe performed a multicentric retrospective study enrolling 570 COVID-19 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In another investigation, AI was harnessed to identify pulmonary vascular-related structures (VRS). This study revealed a correlation between the intensity of care required and an increase in VRS, which emerged as an independent explanatory factor for mortality [29]. The AI system's comparable performance against radiologist-assessed values in predicting clinical outcomes could represent a game-changer for resource-constrained settings [25].…”
Section: Plos Onementioning
confidence: 83%
“…In another investigation, AI was harnessed to identify pulmonary vascular-related structures (VRS). This study revealed a correlation between the intensity of care required and an increase in VRS, which emerged as an independent explanatory factor for mortality [29]. The AI system's comparable performance against radiologist-assessed values in predicting clinical outcomes could represent a game-changer for resource-constrained settings [25].…”
Section: Plos Onementioning
confidence: 83%
“…CALIPER has been utilized in studying interstitial lung disease abnormalities, including its potential as an independent predictor of survival in idiopathic pulmonary fibrosis [ 21 ]. Romei et al first used CALIPER to assess CT scans of COVID-19 pneumonia, and the VRS was demonstrated to be associated with mortality [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of ILD was defined as the sum of the percentages of GGO, reticular abnormalities and honeycombing [ 20 ]. CALIPER allows the computing of the vascular-related structure (VRS) volume, defined as the volume of pulmonary vessels and contiguous-related structures, as perivascular fibrosis [ 22 ]. To calculate this parameter, the software utilizes the eigenvalues of the Hessian matrix, with the purpose being to achieve an optimized multiscale filter enhancing tubular structures, such as pulmonary vessels with a diameter larger than 3 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, another clinical scenario where radiomic features extracted from the spleen were helpful in clinical decision making is COVID-19. The value of lung parenchymal quantitative imaging biomarkers for COVID-19 diagnosis and severity assessment has been already widely proven in the literature [ 39 , 40 , 41 ]. However, COVID-19 is known to also involve other organs [ 42 ].…”
Section: Discussionmentioning
confidence: 99%